(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
The article investigated the historical roots of the predominance of foreign cultural productions in Brazil, analyzing how colonization and European and North American influence shaped the artistic production of the country’s theatrical scene until the 20th century. From the Jesuit drama to the creation of the UFBA Theater School, the research analyzed how the undervaluing of the national scenario and the overvaluing of the foreign one consolidated the so-called "mongrel complex", in which the devaluation of indigenous and African cultures was a central theme, highlighting the need to recognize and value Brazilian cultural diversity in order to overcome its colonial heritage.